A process‐based model supports an association between dispersal and the prevalence of species traits in tropical reef fish assemblages. Issue 12 (26th September 2019) - Donati, Giulia Francesca Azzurra; Parravicini, Valeriano; Leprieur, Fabien; Hagen, Oskar; Gaboriau, Theo; Heine, Christian; Kulbicki, Michel; Rolland, Jonathan; Salamin, Nicolas; Albouy, Camille; Pellissier, Loïc
Abstract : Habitat dynamics interacting with species dispersal abilities could generate gradients in species diversity and prevalence of species traits when the latter are associated with species dispersal potential. Using a process‐based model of diversification constrained by a dispersal parameter, we simulated the interplay between reef habitat dynamics during the past 140 million years and dispersal, shaping lineage diversification history and assemblage composition globally. The emerging patterns from the simulations were compared to current prevalence of species traits related to dispersal for 6315 tropical reef fish species. We found a significant spatial congruence between the prevalence of simulated low dispersal values and areas with a large proportion of species characterized by small adult body size, narrow home range mobility behaviour, pelagic larval duration shorter than 21 days and diurnal activity. Species characterized by such traits were found predominantly in the Indo‐Australian Archipelago and the Caribbean Sea. Furthermore, the frequency distribution of the dispersal parameter was found to match empirical distributions for body size, PLD and home range mobility behaviour. Also, the dispersal parameter in the simulations was associated to diversification rates and resulted in trait frequency matching empirical distributions. Overall, our findings suggest that past habitat dynamics, in conjunction with dispersal processes, influenced diversification in tropical reef fishes, which may explain the present‐day geography of species traits.